The acute effects of simulated hypoxic training at different altitudes on oxidative stress and muscle damage in elite long-distance runners - Sarikaya, Muecahit; Oge, Beyza; Embiyaoglu, Nuri Mert; Selcuk, Muzaffer; Cinar, Vedat; Oner, Salih; Batrakoulis, Alexios (Peerj Inc, 2025)
Background Understanding the impact of altitude on muscle damage and oxidative stress is essential for optimizing training and recovery strategies for athletes exposed to high-altitude conditions. Therefore, this study aimed to investigate the effects of acute exercise at different altitudes on oxidative stress and muscle damage. Methods A total of twelve elite long-distance runners (mean age: 20.3 +/- 1.5 years) from different branches participated in the study. The exercise protocol was the Bruce submaximal treadmill exercise test, which was conducted under three simulated hypoxic conditions (at 1,700 m, 2,450 m, and 3,200 m) and one normoxic condition (sea level). All measurements took place at the same time of the day. After the exercise protocol, 5 ml venous blood samples were taken from the participants, while heart rate and oxygen saturation were monitored at the 3rd, 6th, 9th, and 12th minutes during the exercise. Results Significant altitude-dependent variations were observed in oxidative stress markers, with total oxidant status (TOS) (p = 0.017) and malondialdehyde (MDA) (p < 0.001) levels increasing at higher altitudes, while total antioxidant status (TAS) (p < 0.001) exhibited an elevation and oxidative stress index (OSI) (p < 0.001) demonstrated a decline as altitude increased. However, no significant difference was found in creatine kinase (CK, p = 0.059) levels. Additionally, there were significant differences in the oxygen saturation measurement taken at the 3rd (p < 0.001), 6th (p < 0.001), 9th (p < 0.001), and 12th (p < 0.001), minutes following the exercise session. There was no difference in the pulse measurement taken at the 3rd and 12th minutes, but a difference was observed at the 6th and 9th minutes post-exercise (p < 0.01). Conclusions In conclusion, the study determined that endurance exercises performed under simulated normobaric hypoxia at different altitudes increased TAS and reduced OSI in elite long-distance runners. The increase in TAS and the reduction in OSI were more pronounced at higher altitudes, particularly at 2,450 m and 3,200 m, compared to sea level. These findings highlight the need for altitude-specific training and recovery strategies to minimize oxidative stress and muscle damage in athletes.
Keywords: Hypoxia; Training; Oxidative stress; Muscle damage; Altitude